The Weight Is Over: RN First Assisting Techniques for Laparoscopic Sleeve Gastrectomy. (28th July 2015) - Wentzell, Joanne; Neff, Marc
Abstract: Obesity‐related laparoscopic sleeve gastrectomy is a common yet technically challenging bariatric procedure that requires specialized surgical knowledge and training for OR personnel. Critical components of care include an effective preoperative assessment, positioning of the patient, and operation and maintenance of laparoscopic equipment and instrumentation. The purpose of this article is to explain the steps of laparoscopic sleeve gastrectomy and illustrate principles and surgical techniques for the RN who is first assisting during the procedure. Also provided is a perioperative nursing care plan for the patient undergoing bariatric surgery, to aid perioperative nurses in understanding the sequence of events and special considerations for this patient population.